1986
DOI: 10.1016/s0735-1097(86)80433-8
|View full text |Cite
|
Sign up to set email alerts
|

Valve replacement in children less than 5 years of age

Abstract: Between 1966 and 1984, there were 63 children less than 5 years of age who underwent 70 valve replacements (49 mitral [5 repeat], 6 aortic, 11 tricuspid [systemic ventricle; 2 repeat]), 2 tricuspid [pulmonary ventricle] and 1 multiple [mitral-aortic]) at Children's Hospital. Tissue valves were used in 20%. Since 1980, only Björk-Shiley and St. Jude valves have been used. The most common indication for valve replacement was mitral regurgitation after repair of atrioventricular (AV) canal (34%). Mortality droppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…TE and bleeding events are uncommon with this therapy. [590][591][592][593][594] There is no direct evidence describing optimal thromboprophylaxis in children with bioprosthetic heart valves. Recommendations, therefore, must rely on indirect evidence from adults and the associated recommendations.…”
Section: 40-242 Biologic and Mechanical Prosthetic Heart Valvesmentioning
confidence: 99%
“…TE and bleeding events are uncommon with this therapy. [590][591][592][593][594] There is no direct evidence describing optimal thromboprophylaxis in children with bioprosthetic heart valves. Recommendations, therefore, must rely on indirect evidence from adults and the associated recommendations.…”
Section: 40-242 Biologic and Mechanical Prosthetic Heart Valvesmentioning
confidence: 99%
“…Spevak et al [119] found that only 64% of the treated children maintained a PT within the desired range on at least 50% of the measurements. Streif et al [120] found, in a pediatric OAT clinic including a total of 319 children, that the percentage of INR measurements within target range depended on age and therapeutic INR target range; under the age of 1 year time within therapeutic INR target range was 37% ± 16 (mean ± 1 SD) rising up to 53% ± 19 for patients between 13 and 18 years.…”
Section: Childrenmentioning
confidence: 99%
“…In a subset of 11 children within their larger sample who had regular checks of PT, Spevak et al 9 found that only 64% of those children maintained a PT within the desired range on at least 50% of the measurements. Another factor to consider is the patient's compliance with the monitoring regimen.…”
Section: Monitoring and Dosage Adjustmentmentioning
confidence: 99%